Architecture - re-Construction - Geometry: a knowledge path applied to the study of Plantery's vaults in Turin - Roberta Spallone; Marco Vitali (Disegnare con, 2012)
Plantery's vaults, by the name of the architect working in Turin since first years of '700, are composed by a main vault intersected by some axial and angular secondary vaults. Plantery's vaults allow to roof over unitary spaces obtaining effects of lightness also by small rises. Their diffusion, up to the '80s of the century, in boardrooms as palaces halls, and the richness of variations on the theme, justifies a research, that makes use of survey and digital modeling. This research is focused on the relationships between geometric models and built architecture, connected by use of materials, construction techniques and decorative styles.